UPAYA PENINGKATAN PENGETAHUAN DAN SIKAP KADER POSYANDU DALAM DETEKSI DINI FAKTOR RESIKO KEHAMILAN - Rany Muspika Sari; Ismiati Ismiati; PS Kurniawati PS Kurniawati (Poltekkes Kemenkes Bengkulu, 2020)
Abstract: Early detection of high risk of pregnancy can reduce maternal mortality. The introduction of risk factors in pregnant women is carried out proactively by health workers or trained personnel in the community such as cadres. Padang Community Health Center has 9 posyandu with the total number of active cadres 43 people, coverage coverage of high risk pregnant women by 2015 cadres is 2 people (2.50%). This study aims to determine the effect of efforts to increase knowledge and attitude of posyandu cadres in early detection of pregnancy risk factors. This research uses quasy experimental method with one group pre-post test design. The sample of this research is all posyandu cadres in working area of Padang Serai Community Health Center is 43 people. The result of bivariate analysis with paired t-test showed significant difference of knowledge and attitude of respondent before and after intervention. Ie on pretest-posttest1 knowledge p = 0.000 <0.05, pretest-posttest2 p = 0,000 <0.05, on posttest-posttest2 p = 0.007 <0.05. On the attitude of pretest-posttest1 value p = 0.000 <0,05, pretest-posttest2 p = 0,000 <0,05, on posttest-posttest2 p = 0.000 <0,05, indicate that there is influence of effort to increase knowledge and attitude of posyandu cadre in detection Early pregnancy risk factors.Keywords : knowledge, attitudes, early detection of risk factors for pregnancy.